Food science and food biotechnology - Gutiérrez-López, Gustavo F.; Barbosa-Cánovas, Gustavo V. (CRC Press, 2003)
his groundbreaking book provides a balanced and organized discussion of the interactions of food science and biotechnology at the molecular and industrial levels. Carefully selected and reviewed contributions stress the aspects of modern bioprocessing, analysis, and quality control that are common to both food science and biotechnology. The detailed analysis of specific examples of upstream and downstream processes assists readers in understanding the underlying principles and the similarities between applications. Throughout the book there is a strong emphasis on emerging technologies, combined methods of preservation of food and biological materials, and descriptions of state-of-the-art equipment and techniques.